Liver‐related deaths in HIV‐infected patients between 1995 and 2010 in France: the Mortavic 2010 study in collaboration with the Agence Nationale de Recherche sur le SIDA (ANRS) EN 20 Mortalité 2010 survey1. Issue 4 (18th December 2014) - Rosenthal, E; Roussillon, C; Salmon‐Céron, D; Georget, A; Hénard, S; Huleux, T; Gueit, I; Mortier, E; Costagliola, D; Morlat, P; Chêne, G; Cacoub, P; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to describe the proportion of liver‐related diseases (LRDs) as a cause of death in HIV‐infected patients in France and to compare the results with data from our five previous surveys. Methods In 2010, 24 clinical wards prospectively recorded all deaths occurring in around 26 000 HIV‐infected patients who were regularly followed up. Results were compared with those of previous cross‐sectional surveys conducted since 1995 using the same design. Results Among 230 reported deaths, 46 (20%) were related to AIDS and 30 (13%) to chronic liver diseases. Eighty per cent of patients who died from LRDs had chronic hepatitis C, 16.7% of them being coinfected with hepatitis B virus (HBV). Among patients who died from an LRD, excessive alcohol consumption was reported in 41%. At death, 80% of patients had undetectable HIV viral load and the median CD4 cell count was 349 cells/μL. The proportion of deaths and the mortality rate attributable to LRDs significantly increased between 1995 and 2005 from 1.5% to 16.7% and from 1.2‰ to 2.0‰, respectively, whereas they tended to decrease in 2010 to 13% and 1.1‰, respectively. Among liver‐related causes of death, the proportion represented by hepatocellular carcinoma (HCC) dramatically increased from 5% in 1995 to 40% in 2010 (p = 0.019). Conclusions The proportion of LRDs among causes of death in HIV‐infected patients seems recently to have reached a plateau after a rapid increase during the decade 1995−2005. LRDs remain a leading cause of death in this population, mainly as a result of hepatitis C virus (HCV) coinfection, HCC representing almost half of liver‐related causes of death.